Artificial Intelligence (IntechOpen, 2023)
Artificial intelligence (AI) is a potent buzzword and happening technology which has greatly impacted the lifestyle of every human being either directly or indirectly and is shaping the future of tomorrow. In fact, AI is fast becoming an intrinsic part of our daily life and is not confined to university research labs, even if remarkable progress has been made in this domain. The benefit of this phenomenon is widely recognized in diversified areas, ranging from medicine to security to consumer applications and business, and resulting in improvements in the quality of life of humankind. Every new disruptive technology has its own pros and cons and AI is no exception to this rule. Privacy, data protection, and the rights of individuals pose social and ethical challenges.